Effects of potassium application and soil moisture on the growth of Corymbia citriodora plants - Sá, Ariadne Felício Lopo De; Valeri, Sérgio Valiengo [UNESP]; Cruz, Mara Cristina Pessoa Da [UNESP]; Barbosa, José Carlos [UNESP]; Rezende, Gustavo Machado [UNESP]; Teixeira, Matheus Pozzetti [UNESP] (UFLA - Universidade Federal de Lavras, 2014)
The objective of this work was to evaluate the effects of potassium and soil moisture levels on the growth of Corymbia citriodora plants. Four doses of potassium were applied (0, 40, 80 and 120 mg.dm-3) and three soil moisture levels were established(50-80%, 65-80% and 80% of maximum soil field capacity). The experiment was a 4x3 factorial arrangement of treatments within a randomized complete design with six replications for each treatment and one pot with two plants for each plot. At 90 days after planting, the plant growth parameters: survival rate, height, stem diameter, leaf area, relative chlorophyll concentration, leaf dry mass, stem and branches dry mass, root dry mass, total dry mass and leaf macronutrient contents were measured. High soil moisture content is necessary for Corymbia citriodora seedlings at nursery stage. Effects of the K doses were not observed in plants, even when they were cultivated in a soil with a low content of this nutrient.

Conduziu-se este trabalho, com o objetivo de avaliar os efeitos de doses de potássio e umidades do solo no crescimento de plantas de Corymbia citriodora. Foram aplicadas quatro doses de potássio (0, 40, 80, e 120 mg.dm-3) e promovidas três níveis de umidades do solo (50-80%, 65-80% e 80% do volume máximo de água retido pelo solo em vaso), combinadas em um esquema fatorial 4x3. O delineamento experimental foi inteiramente casualizado com seis repetições, e cada parcela foi composta por um vaso contendo duas plantas. Aos 90 dias após o plantio, foram avaliados: porcentagem de sobrevivência, altura, diâmetro do caule, área foliar, teor relativo de clorofila, massa de matéria seca de folhas, de caule e ramos, de raízes e total, e teor de macronutrientes nas folhas. Mudas de Corymbia citriodora necessitam de alta umidade do solo na fase de viveiro. Não foram observados efeitos das doses de potássio nas plantas, mesmo quando a concentração desse nutriente no solo era baixa.
Efeitos da aplicação de potássio e umidades do solo no crescimento de plantas de Corymbia citriodora
Keywords: Eucalipto; Adubação; Déficit hídrico; Nutrição florestal; Seca; Eucalyptus; Fertilization; Water deficit; Forest nutrition; Drought